2014
DOI: 10.1016/j.ejmech.2014.10.024
|View full text |Cite
|
Sign up to set email alerts
|

1H-1,2,3-triazole tethered isatin-ferrocene conjugates: Synthesis and in vitro antimalarial evaluation

Abstract: 1H-1,2,3-triazole tethered isatin-ferrocene conjugates were synthesized and evaluated for their antiplasmodial activities against chloroquine-susceptible (3D7) and chloroquine-resistant (W2) strains of Plasmodium falciparum. The conjugates 5f and 5h with an optimum combination of electron-withdrawing halogen substituent at C-5 position of isatin ring and a propyl chain, introduced as linker, proved to be most potent and non-cytotoxic among the series with IC50 values of 3.76 and 4.58 μM against 3D7 and W2 stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 42 publications
0
43
0
1
Order By: Relevance
“…C‐5 substituted isatins and CPFX were alkylated with 1,2‐dibromoethane and propargyl bromide, respectively, in the presence of potassium carbonate to afford the corresponding N ‐(2‐bromoethyl)isatins 2a – d (yield: 51–67%) and propargyl CPFX 4 (yield: 42%) via literature methods . Subsequently, treatment of N ‐(2‐bromoethyl)isatins 2a – d with sodium azide at 60°C provided the desired azido precursors 3a – d . The precursors 3a – d and 4 were used to synthesize desired 1,2,3‐triazole‐tethered hybrids 5a – d (yield: 22–35%) via Cu‐promoted azide‐alkyne cycloaddition reaction in the presence of CuI and TEA in MeCN/DCM ( v:v = 1:1) .…”
Section: Resultsmentioning
confidence: 99%
“…C‐5 substituted isatins and CPFX were alkylated with 1,2‐dibromoethane and propargyl bromide, respectively, in the presence of potassium carbonate to afford the corresponding N ‐(2‐bromoethyl)isatins 2a – d (yield: 51–67%) and propargyl CPFX 4 (yield: 42%) via literature methods . Subsequently, treatment of N ‐(2‐bromoethyl)isatins 2a – d with sodium azide at 60°C provided the desired azido precursors 3a – d . The precursors 3a – d and 4 were used to synthesize desired 1,2,3‐triazole‐tethered hybrids 5a – d (yield: 22–35%) via Cu‐promoted azide‐alkyne cycloaddition reaction in the presence of CuI and TEA in MeCN/DCM ( v:v = 1:1) .…”
Section: Resultsmentioning
confidence: 99%
“…N ‐(2‐Bromoethyl)isatins 2a – d (yield: 51–67%) and propargyl CPFX 4 (yield: 42%) via literature methods by alkylation of the corresponding isatins and CPFX with 1,2‐dibromoethane and propargyl bromide in the presence of potassium carbonate. Treatment of N ‐(2‐bromoethyl)isatins 2a – d with sodium azide at 60°C provided the desired azido precursors 3a – d , which was used along with 4 to synthesize 5a – d (yield: 31–46%) via Cu‐promoted azide‐alkyne cycloaddition reaction in the presence of Cu(OAc) 2 in DMF . Finally, condensations of targets 5a – d with various amine hydrochloride in the presence of sodium bicarbonate formed CPFX‐isatin‐1 H ‐1,2,3‐triazole hybrids 6a – l (18–41%) .…”
Section: Resultsmentioning
confidence: 99%
“…A rapid analysis of our data has clearly demonstrated that the presence of a chlorophenyl group associated with a p-methoxyphenyl substituent on the b-lactam ring enhances the antimalarial activity. Otherwise, it has been recently reported that azole derivatives could be inhibitors of Falcipain-2, a papain family cysteine protease and important hemoglobinase of erythrocytic Plasmodium falciparum parasites (Kumar et al, 2014a, b). In this context, further studies are now under current investigation to elucidate the mechanism of action involved by our molecules against Falcipain-2 in order to improve their structure-activity relationships.…”
Section: Resultsmentioning
confidence: 96%